Accumulation of salts in the soil and growth of cowpea under salinity and phosphorus fertilization - Lima, Yuri; Sá, Francisco Vanies; Ferreira Neto, Miguel; Paiva, Emanoela; Gheyi, Hans (Revista Ciência Agronômica, 2017)
Cowpea is widely grown in the Brazilian semiarid region, however, due to excess salts in the soil and irrigation water constantly low crop productivity has been observed. Accumulation of salts in the soil, growth and biomass partition of cowpea under salt stress and phosphorus fertilization was evaluated in this study. The assay was conducted in a greenhouse in Mossoró, State of Rio Grande do Norte, Brazil, from September to December 2015, using a Alfissol Latosolic with low phosphorus content. The experiment was carried out in a randomized block design in a factorial 5 x 3 arrangement, consisting of five water salinity levels (0.5, 1.5, 2.5, 3.5 and 4.5 dS m-1) and three doses of superphosphate (60, 100 and 140% of the recommended dose for crop - 60 kg ha-1 of P2O5), with five repetitions. The plants of cowpea cv. Paulistinha were cultivated for 49 days after sowing in lysimeters with 8 dm3 capacity. During this period was determined the accumulation of salts in the soil, growth and biomass partition plants. Water with salinity higher than 1.5 dS m-1 increased soil salinity above the crop’s threshold of 4.9 dS m-1, 21 days after sowing. Increased salinity impaired growth and biomass partition of cowpea plants, with greater accumulation of dry matter in the leaves and stem in comparison to the root. Hinghest dose of superphosphate promoted greater growth of cowpea plants.